Implementation of an RFID-based management system for operation room - Po-Jen Chen; Yung-Fu Chen; Sin-Kuo Chai; Yung-Fa Huang (2009 International Conference on Machine Learning and Cybernetics, 2009)
Surgery-related error, second to drug-related error, is one of the most commonly found medical errors resulting in premature deaths of patients. Improvement of operation room (OR) environment through efficient OR management, surgical procedure check, personnel communication, and information transmission can highly elevate the patient safety. In this study, radio frequency identification (RFID) was used to enhance the OR management (ORM) information system for efficient identification of patients and healthcare providers, tracking of critical surgery procedures, and control of medications and medical materials to prevent medical errors. A prototypic system which composes of console, operation room, surgery room, and recovery room subsystems is presented. Preliminary clinical application was tested in the surgical department of a hospital near Taichung area. The result demonstrated that it is useful in preventing medical errors under surgical setting. Further evaluation of efficiency has to be done in the future.